Impact of Educational Levels and Health Literacy on Community Acetaminophen Knowledge. (December 2015) - Ip, Eric J.; Tang, Terrill T-L.; Cheng, Vincent; Yu, Junhua; Cheongsiatmoy, Derren S.
Patient understanding of acetaminophen is important for its safe and appropriate self-use. A cross-sectional survey was conducted in the San Francisco Bay Area to determine the impact of educational level, patient health literacy score, and other demographic characteristics on acetaminophen knowledge. A 17-item, in-person, paper-and-pen questionnaire containing questions about demographics and acetaminophen knowledge was administered to 311 adults outside 5 local grocery stores in varying socioeconomic communities. Knowledge assessed was whether Tylenol–McNeil contains acetaminophen, maximum daily dose, and primary organ affected by toxicity. Participant health literacy was evaluated using the Rapid Estimate of Adult Literacy in Medicine-Short Form (REALM-SF) test. Of the 300 who successfully completed the study, only 3.8% of all subjects were able to answer all 3 acetaminophen knowledge questions correctly regardless of educational level or health literacy score. This reaffirms that a lack of appropriate acetaminophen knowledge remains present in the general population, and further efforts to educate patients will be needed to prevent adverse events.